To do these, start by looking at the "b" value -6.
divide it by 2
-6/2 = -3
now square this number
(-3)^2 = 9
this is what you need for the "c" value
there is only a 5 for the c value so add 4 to both sides of the equation. ( +4 = +4)
y +4 = x^2 -6x +5 +4
y +4 = x^2 -6x +9
y +4 = (x -3)^2
y = (x -3)^2 - 4
vertex ( 3, -4) upwards facing like a bowl, because the "a" value is positive. So the vertex is the minimum, lowest point on the graph.
<span>(x-7)^2 = (x-7)(x-7) = x^2 -7x -7x +49 = x^2-14x+49</span>
answer is 'x^2+14x+49'
Answer:
A
<em>Hope that helps!</em>
Step-by-step explanation:
Steps:
A=bh/2
A= (18ft)(6ft)
_______
2
A = 108
____
2
A= 54ft^2